Optimization Of Polyhydroxyalkanoate (PHA) Production By Burkholderia Cepacia BPT1213 Using Waste Glycerol As The Sole Carbon Source - Mohd Zain, Nor Fauziah (2017)
Polyhydroxyalkanoate (PHA) is touted as an environmental friendly alternative to recalcitrant petrochemical derived plastics. Due to high production cost issue, waste glycerol produced from biodiesel industry has potential as cheaper carbon source for PHA synthesis by microorganisms. The objectives of this study were to optimize and scale up the production of PHA by a local isolate, Burkholderia cepacia BPT1213, from the shake flask system to a 2.5 L bioreactor system. Throughout this study, the strain was grown in minimal salt medium (MSM) supplemented with 2% (v/v) of waste glycerol (86.70% purity), a by-product of the production biodiesel from palm oil as the sole carbon source.